An escape from the world: Gilles Clement's travelogue to the Reunion and Madagascar islands - Ávila Calzada, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Travelogues have been, throughout history, a valuable tool for describing the experiences and observations of the traveller, may they be scientists, artists, architects or landscape architects. A combination of texts and drawings, this type of documents survive in our times despite the ease in the exchange of information through current digital media. They reflect the subjective gaze of the traveller, who highlights those aspects that arouse greater interest. It is in this subjective component that the interest of these field diaries lies, showing us the mental and creative processes that arise from these life experiences, and which are sometimes reflected in the authors’ subsequent projects or writings. In March 1995, Gilles Clément, one of the most paradigmatic landscape designers of the last decades, travelled to the islands of La Réunion and Madagascar with the aim of developing two very different projects. The story of this journey is reflected in an unpublished travelogue, object of this article, in which the author recounts his journey in detail through descriptions, personal reflections, annotations and anecdotes, illustrated with drawings and sketches.
Keywords: Gilles Clément; Maïdo; Travelogue; Madagascar; La Reunión; Landscape architecture